Processo de captação de recursos para redes de infraestrutura urbana em pequenos e médios municípios do norte do estado do Rio Grande do Sul - Oliveira, Ivânia Regina de (2018)
Society seeks better infrastructure conditions in cities with a view to improving economic, urban and social developments. As cities grow, infrastructure networks need expansions and that require investment. Capital and infrastructure management is complex, involves the planning, execution and monitoring of urban development programs and projects for mobility, water supply, sewage collection and treatment, waste collection, among other services. After the constitutional changes of 1988,the municipalities received new attributions and began to have a greater participation in the provision of public goods and services.Given the budgetary difficulties of the municipalities, which do not have the resources to carry out all the works and their other obligations, one of the alternatives for making investments in infrastructure feasible is the search for financialresources, either through a transfer from the federal government or through financing. This work investigates the capture process and the sources of resources for urban infrastructure networks. The objective of this study was to characterize the resource capture process for urban infrastructure networks, identifying the sources of resources available to small and medium-sized municipalities in the northern region of the of Rio Grande do Sul, state, Brazil. The study was divided into stages and phases that included data collection, characterization, systematization and analysis that resulted in the presentation of the fundraising process and the main sources of funds or financing. Eleven municipalities of the Northern region of Rio Grande do Sul were selected, according to a study of the Influence Regions of IBGE Cities (2007), which defines the hierarchy of urban centers. For analysis, the technique of content analysis was used through categories and subcategories defined according to the specific objectives established. Municipalities, although autonomous entities, are extremely dependent on the resources of the Federal Government. The analysis of funds raised reveals that the main modality of fundraising are transfers, by parliamentary amendments. Other alternatives for financing were mapped in international and national financial agents, but little access was made to the following aspects: the difficulty of municipalities to demonstrate financial capacity for payment and the current legislation that establish standards for the management of public finances.